A molecular, morphological and biological characterisation of the genus Globodera (Nematoda: Heteroderidae) in South Africa - Knoetze, Rinus (Stellenbosch : Stellenbosch University, 2014)
Thesis (PhD)--Stellenbosch University, 2014.